Perceived challenges towards Education 4.0 implementation among academicians: a preliminary analysis / Yunita Awang, Azuraidah Taib and Nazuha Muda - Awang, Yunita; Taib, Azuraidah; Muda, Nazuha (2020)
The Industrial Revolution caused major changes in the economy and advancement in technology. Specifically, IR4.0 stimulates the development of Education 4.0, in which the use of information, internet and technology become part of the teaching and learning process allowing students to learn at any time through digital platforms. Promoting for Education 4.0 involved challenges particularly constant changes in the teaching and learning techniques, and the facilities to cater to the technology demands. This study attempts to assess perceived challenges towards Education 4.0 implementation among the academicians at a comprehensive university and to explore the relationship between gender and perceived challenges among them. Based on purposive sampling, online questionnaires were distributed via google form to a population of 352 academicians in the selected comprehensive university. Data gathered from 127 responses were analysed using SPSS. The findings indicate the majority of the respondents perceived IT infrastructure as the main challenge, while the skills of individuals are the least challenges towards Education 4.0 implementation. However, there is no evidence of a significant association between gender and any of the perceived challenges items. Thus, regardless of male or female academicians, they have a similar perception of the challenges towards Education 4.0 implementation. The findings assist the Education 4.0 stakeholders to look into those perceived challenges and take necessary actions such as increasing budget allocation for IT facilities, as a support towards the success of Education 4.0 implementation. Future research may be undertaken to examine more specific infrastructure challenges in implementing education 4.0 at other comprehensive universities as well as at research universities and focused universities.